Schwartz's principles of surgery - Schwartz, Seymour I., 1928-; Brunicardi, F. Charles; Andersen, Dana K.; Billiar, Timothy R.; Dunn, David L.; Hunter, John G.; Matthews, Jeffrey B.; Pollock, Raphael E. (New York : McGraw-Hill, Medical Pub. Division, 2010)
"Written by the world's foremost practitioners and instructors, this landmark reference logically progresses from basic science principles, including topics such as cells, genomics, and molecular surgery, to clinical areas such as the pancreas. From cover to cover, the book reflects a distinctly modern approach to the dissemination of surgical knowledge, providing up-to-date coverage of all key surgical areas, from trauma and transplantation, to neurosurgery. In each chapter, this context is supported by a skill-building presentation that includes boxed key points, detailed anatomical figures, diagnostic and management algorithms, and key references." "For every kind of procedure, this trusted clinical companion helps you meet the sequential demands in the care of surgical patients, leading to the best possible outcomes."--Jacket.
Accreditation council for graduate medical education core competencies -- Systemic response to injury and metabolic support -- Fluid and electrolyte management of the surgical patient -- Hemostasis, surgical bleeding, and transfusion -- Shock -- Surgical infections -- Trauma -- Burns -- Wound healing -- Oncology -- Transplantation -- Patient safety -- Physiologic monitoring of the surgical patient -- Minimally invasive surgery, robotics, and natural orifice transluminal endoscopic surgery -- Molecular and genomic surgery -- The skin and subcutaneous tissue -- The breast -- Disorders of the head and neck -- Chest wall, lung, mediastinum, and pleura -- Congenital heart disease -- Acquired heart disease -- Thoracic aneurysms and aortic dissection -- Arterial disease -- Venous and lymphatic disease -- Esophagus and diaphragmatic hernia -- Stomach -- The surgical management of obesity -- Small intestine -- Colon, rectum, and anus -- The appendix -- Liver -- Gallbladder and the extrahepatic biliary system -- Pancreas -- Spleen -- Abdominal wall, omentum, mesentery, and retroperitoneum -- Soft tissue sarcomas -- Inguinal hernias -- Thyroid, parathyroid, and adrenal -- Pediatric surgery -- Urology -- Gynecology -- Neurosurgery -- Orthopedic surgery -- Surgery of the hand and wrist -- Plastic and reconstructive surgery -- Surgical considerations in the elderly -- Anesthesia of the surgical patient -- Ethics, palliative care, and care at the end of life.
Includes bibliographical references (pages 1769-1776) and index.
Keywords: Surgery; Surgical Procedures, Operative